The Study of Comparative Literature as A Science - N., Toshmatova (International Journal on Orange Technologies, 2021)
This article provides theoretical information about the development of comparative literature and comparative-historical literature and the formation of these areas as a science. The scientific conclusions of Eastern and Western scholars in this regard are also included in this article.